Spectrophotometric and HPTLC Method for SimultaneousEstimation of Pantoprazole and Domperidone inTheir Pharmaceutical Preparations - Kakde, R.B.; Gedam, S.N.; Kasture, A.V. (Asian Journal of Chemistry, 2010)
A simple, rapid, spectrophotometric and HPTLC method has been developed for the simultaneous estimation of pantoprazole and domperidone in their pharmaceutical preparations. Developed spectrophotometric method employs simultaneous equations method to estimate both the drugs in the formulation. Pantoprazole and domperidone showed maximum absorbance at 331 and 284 nm, respectively. Pantoprazole and domperidone obeyed Beer Lambert's law in the concentration ranges from 10–50 and 10–50 μg/mL, respectively. In HPTLC method, the mobile phase consists of acetone : toluene : methanol : glacial acetic acid (2 : 8 : 2 : 0.1) using a precoated silica gel 60 F254 TLC plate. The plate was scanned by computer controlled HPTLC scanner with Camag Cats software and quantified at 298 nm. Both the methods were found to be precise and accurate and can be adopted in routine analysis of drugs in formulation.